Consensus for the management of pancreatic exocrine insufficiency: UK practical guidelines. Issue 1 (17th June 2021) - Phillips, Mary E; Hopper, Andrew D; Leeds, John S; Roberts, Keith J; McGeeney, Laura; Duggan, Sinead N; Kumar, Rajesh
Abstract : Introduction: Pancreatic exocrine insufficiency is a finding in many conditions, predominantly affecting those with chronic pancreatitis, pancreatic cancer and acute necrotising pancreatitis. Patients with pancreatic exocrine insufficiency can experience gastrointestinal symptoms, maldigestion, malnutrition and adverse effects on quality of life and even survival. There is a need for readily accessible, pragmatic advice for healthcare professionals on the management of pancreatic exocrine insufficiency. Methods and analysis: A review of the literature was conducted by a multidisciplinary panel of experts in pancreatology, and recommendations for clinical practice were produced and the strength of the evidence graded. Consensus voting by 48 pancreatic specialists from across the UK took place at the 2019 Annual Meeting of the Pancreatic Society of Great Britain and Ireland annual scientific meeting. Results: Recommendations for clinical practice in the diagnosis, initial management, patient education and long term follow up were developed. All recommendations achieved over 85% consensus and are included within these comprehensive guidelines.